2017
DOI: 10.3945/ajcn.117.156034
|View full text |Cite
|
Sign up to set email alerts
|

Dietary iron intake, iron status, and gestational diabetes

Abstract: Pregnant women are particularly vulnerable to iron deficiency and related adverse pregnancy outcomes and, as such, are routinely recommended for iron supplementation. Emerging evidence from both animal and population-based studies, however, has raised potential concerns because significant associations have been observed between greater iron stores and disturbances in glucose metabolism, including increased risk of type 2 diabetes among nonpregnant individuals. Yet, the evidence is uncertain regarding the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 77 publications
(128 reference statements)
1
63
2
6
Order By: Relevance
“…In contrast to the results of our study, other studies did report associations between intakes of individual micronutrients and risk of developing GDM. A recent review summarized the limited evidence suggesting an association between higher intake of iron, particularly heme iron, and higher risk of GDM [45]. In our study, we observed a 30% increased risk of GDM in women with inadequate iron intakes, but this was not statistically significant, and we were not able to distinguish between heme and non-heme iron intakes.…”
Section: Accepted Manuscriptcontrasting
confidence: 90%
“…In contrast to the results of our study, other studies did report associations between intakes of individual micronutrients and risk of developing GDM. A recent review summarized the limited evidence suggesting an association between higher intake of iron, particularly heme iron, and higher risk of GDM [45]. In our study, we observed a 30% increased risk of GDM in women with inadequate iron intakes, but this was not statistically significant, and we were not able to distinguish between heme and non-heme iron intakes.…”
Section: Accepted Manuscriptcontrasting
confidence: 90%
“…Ferritin, a key protein regulating iron metabolism, is an important clinical determinant of iron status [19][20][21][22]. Multiple experimental studies [7,8,[23][24][25][26] have shown that serum ferritin levels are significantly higher in women with GDM than in women without GDM. Moreover, serum ferritin levels have been found to strongly correlate with levels of plasma glucose, insulin and HbA1c, and elevated ferritin is an independent risk factor for the development of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Yet adaptations of iron homeostasis to pregnancy and early infancy raise the possibility that higher absorption rates might, with high intakes, result in excess iron exposure in those who are iron replete or have high stores, but further research is needed to examine this possibility. Excess iron accumulates preferentially in some target tissues, such as the brain, stem cells, and erythropoietic cells (36) as well as the pancreas (37). As a pro-oxidant, excess iron can result in increased reactive oxygen species, oxidative stress, and potentially oxidative damage (36).…”
Section: Supplementing Iron-replete Pregnant Women and Young Childrenmentioning
confidence: 99%
“…Emerging evidence of adverse outcomes of supplementation or high iron status in iron-replete pregnant women and young children derives from studies in both developed and developing countries linking high iron status to a variety of health outcomes including GDM (observational case-control and prospective cohort studies and limited randomized controlled trials), preterm birth (observational studies and randomized controlled trials), and impaired fetal growth (observational studies) (2,33,37). The nature of this evidence is summarized in the evidence map presented in Table 1 in terms of the types of evidence (mechanistic, observational, or randomized controlled trials) with a summary of the nature of the totality of the evidence.…”
Section: Supplementing Iron-replete Pregnant Women and Young Childrenmentioning
confidence: 99%
See 1 more Smart Citation